Paste-Injection of Low-Density Barium Hexaferrite Magnets with Soft Magnetic Iron Phase - Wannisa Thongsamrit; Pongsakorn Jantaratana; Thanida Charoensuk; Chitnarong Sirisathitkul (Metals, 2022)
Permanent magnets of varying shapes and sizes are increasingly produced. For hexaferrite magnets, it is challenging to incorporate polymers and a soft magnetic phase in the form of paste before injection molding or extrusion free-forming. In this study, hard magnetic barium hexaferrite/soft magnetic iron composites with a density of 2.28–2.34 g/cm3 are obtained after paste-injection molding and subsequent sintering at 1150 °C for 5 h. Variations of the binder (143.5–287.0 mg poly(vinyl alcohol), PVA) and the plasticizer (75–150 mg poly(ethylene glycol), PEG-400) in the ceramic–polymer paste give rise to comparable remanent magnetization (33.10–33.63 emu/g) and coercivity (3854–3857 Oe). Unlike all-ferrite systems, the presence of a soft magnetic metal phase is not detrimental to the coercivity. However, the remanent and saturation magnetizations are not substantially increased. The addition of 1% and 5% of iron oxide in the ceramic–polymer paste gives rise to hard/soft composites with lower densities of 2.11 and 2.14 g/cm3. The coercivity is increased to 3942–3945 Oe; however, the maximum energy product is reduced.
Keywords: Magnetic Properties of Alloys; Magnetic Properties and Synthesis of Ferrites; Electromagnetic wave absorption materials